2018
DOI: 10.1016/j.jcol.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Surgical and oncological short-term outcomes of prone extralevator abdominoperineal excision for low rectal cancer

Abstract: Introduction  In recent years, a standardized surgical approach for low rectal cancer was proposed and adopted in many centres. The extralevator abdominoperineal excision introduce an extensive resection of the pelvic floor and demonstrated superiority if the procedure is done in the prone jack-knife position, especially regarding intraoperative perforation and circumferential resections margins. The aim of this study is to evaluate the surgical and oncological short-term outcomes of prone extralevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…This new technique showed better oncological results by minimizing “surgical waisting” at the level of the puborectal muscle, which is the main cause of positive CM and tumoral or mesorectal perforations 57 . The reason for the superiority of the oncological results and the radicality of the new technique is that in APEs, the levator muscles and the mesorectum are removed en bloc together with the anal canal 58 …”
Section: Extralevator Abdominoperineal Excisions (Apes) Can Benefit Patients With Low Rectal Cancer Especially In Advanced Tumors That Afmentioning
confidence: 97%
See 3 more Smart Citations
“…This new technique showed better oncological results by minimizing “surgical waisting” at the level of the puborectal muscle, which is the main cause of positive CM and tumoral or mesorectal perforations 57 . The reason for the superiority of the oncological results and the radicality of the new technique is that in APEs, the levator muscles and the mesorectum are removed en bloc together with the anal canal 58 …”
Section: Extralevator Abdominoperineal Excisions (Apes) Can Benefit Patients With Low Rectal Cancer Especially In Advanced Tumors That Afmentioning
confidence: 97%
“…57 The reason for the superiority of the oncological results and the radicality of the new technique is that in APEs, the levator muscles and the mesorectum are removed en bloc together with the anal canal. 58 Although the results of recently published systematic reviews comparing ELAPE and conventional APE are not yet conclusive with regard to the superiority of one technique over the other, [59][60][61][62][63][64] ELAPE may be indicated in the treatment of low rectal cancer to avoid the adverse oncological results of inadvertent perforations and positive circumferential resection margins (CRMs) that are associated more closely with the conventional technique. Surgery is indicated mainly for tumors of the lower and ultra-low rectum, especially when the involvement of levator ani muscles are suspected or confirmed.…”
Section: Level Of Evidence: II Grade Of Recommendation: Amentioning
confidence: 99%
See 2 more Smart Citations
“…In the last JCOL number, the National Cancer Institute presents a retrospective series of ELAPE performed from 2003 to 2015, confronting fifty patients undergoing standard APEs against 22 ELAPE. 15 All patients received nCRT and were operated in the prone position. According to the authors, ELAPE was indicated selectively in cases of sphincter complex or levator invasion, and a routine indication could not be established due to the increased perineal complications.…”
mentioning
confidence: 99%